A Meta-Individual Account of Personality Studies - Dorfman, Leonid; Barashkova, Elena (Journal of Psychology and Psychotherapy Research, 2018)
A meta-individual account of personality studies is shown as a kind of dual-system models. Numerous dual-system models in cognitive, personality, and social psychology have received attention. In the above list, the meta-individual world theory would also be worth noting. What is the notion of the meta-individual world? The term ‘meta’ has both epistemic and ontological meanings. On the epistemic view, the meta-individual systems approach assumes a generic model of some portion of reality supplemented with partial confluence theories. It is a kind of meta-theoretical principles, which explicitly or implicitly guide empirical research. On the ontological view, the meta-individual world conceives of a personality extension in a larger system, namely, both the personality itself and its reach beyond its body, extending to a closer social setting. Two principles lie at the core of the meta-individual world theory: duality and complementarity. They lead to a structuralist account which opens multi-dimensionality of personality. 1 An earlier version of this paper was presented at the 2nd International conference “Science, Technology, and Art Relations – STAR” (Tel Aviv, Israel, 19?21 November 2014). A longer version of this paper has appeared in the URL: http://engineers.org.il/_Uploads/12583STAR2-Papers Abstracts.-pdf, (pp. 65-80). [1].